Identification of biological risk factors for persistent postoperative pain after total knee arthroplasty. Issue 3 (17th December 2021) - Sideris, Alexandra; Malahias, Michael-Alexander; Birch, George; Zhong, Haoyan; Rotundo, Valeria; Like, Brian J; Otero, Miguel; Sculco, Peter K; Kirksey, Meghan
Abstract : Background: There is growing evidence that cytokines and adipokines are associated with osteoarthritis (OA) severity, progression, and severity of associated pain. However, the cytokine response to total knee arthroplasty (TKA) and its association with persistent postoperative pain is not well understood. This study aims to describe the perioperative systemic (plasma) and local (synovial fluid) cytokine profiles of patients who do and do not develop persistent pain after TKA. Methods: Patients undergoing primary unilateral TKA for end-stage OA were prospectively enrolled. Demographic and clinical data were gathered preoperatively and postoperatively. Synovial fluid was collected pre arthrotomy and plasma was collected at multiple time points before and after surgery. Persistent postoperative pain (PPP) was defined as Numerical Rating Score≥4 at 6 months. Cytokine levels were measured using the V-Plex Human Cytokine 30-Plex Panel (Mesoscale—Rockville, Maryland, USA). Cytokine levels were compared between PPP and minimal pain groups. Given that the study outcomes are exploratory, no adjustment was performed for multiple testing. Results: Incidence of persistent pain at 6 months post TKA was 15/162 (9.3%). Postoperative plasma levels of four cytokines were significantly different in patients who developed persistent postoperative pain: interleukin (IL)-10, IL-1β, vascular endothelial growth factor, and IL12/IL23p40. Significantly lower IL-10 levels in the prearthrotomy synovial fluid were associated with development of postoperative persistent pain. Conclusions: This prospective cohort study described a distinct acute perioperative inflammatory response profile in patients who developed persistent post-TKA pain, characterized by significant differences in four cytokines over the first 2 postoperative days. These results support the growing evidence that the patient-specific biologic response to surgery may influence longer-term clinical outcomes after TKA. Trial registration number: Clinicaltrials.gov NCT02626533 .